2014
DOI: 10.1186/1471-2407-14-958
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM is expressed in triple-negative breast cancers and is inversely correlated with Androgen receptor

Abstract: BackgroundBreast cancer is a heterogeneous disease displaying distinct molecular features and clinical outcome. The molecular profile of triple-negative breast cancers (TNBCs) overlaps with that of basal-like breast cancers that in turn show similarities with high-grade serous ovarian and endometrial carcinoma. L1CAM is an established biomarker for the latter cancers and we showed before that approximately 18% of primary breast cancers are positive for L1CAM and have a bad prognosis. Here we analysed the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 38 publications
2
38
1
Order By: Relevance
“…Zhu et al showed that stimulation of fibroblasts with recombinant TGF-β results in a decreased expression of SMAD7 [54]. In agreement with previous reports in MCF-10A breast cancer cells [55], TGFB1 knockdown also decreased miR-503 expression. MiR-503-mediated repression of SMAD7 therefore appears to be a way to escape the inhibitory effect of SMAD7 on TGF-β and WNT/β-catenin signaling.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Zhu et al showed that stimulation of fibroblasts with recombinant TGF-β results in a decreased expression of SMAD7 [54]. In agreement with previous reports in MCF-10A breast cancer cells [55], TGFB1 knockdown also decreased miR-503 expression. MiR-503-mediated repression of SMAD7 therefore appears to be a way to escape the inhibitory effect of SMAD7 on TGF-β and WNT/β-catenin signaling.…”
Section: Discussionsupporting
confidence: 80%
“…Among the analysed PCa cell lines, the L1CAM mRNA level was highest in the neuroendocrine NCI-H660 cells (Figure 4.9A). In human PCa samples of the ExonArray IGP cohort, L1CAM was negatively correlated to AR expression (Figure 4.9B), which is consistent with earlier reports [55]. In contrast, L1CAM further showed positive correlation with CHGA and SYP (Figure 4.9B) suggesting that it is upregulated when PCa cells lose their epithelial properties.…”
Section: L1cam Is a Marker Of Ne Differentiation In Pca Cellssupporting
confidence: 81%
See 2 more Smart Citations
“…In the context of EMT up-regulation of L1CAM has been reported to be induced by β-catenin and SLUG [9,16,17]. Down-regulation of L1CAM was found to be driven by the androgen receptor [18], neural restrictive silencer factor/ RE1 silencing transcription factor (NRSF/REST) [19] and PAX-2/8 [20]. Importantly, in endometrial carcinoma cell lines L1CAM has also been shown to be inhibited by DNA methylation of its promoter [21] and by various miRNAs whereby the most reliable data exist for miR-34a [22].…”
Section: Introductionmentioning
confidence: 99%